ZINC ANODE ANALYSIS USED KRI WITH COMPOSITION AND POTENTIAL CORROSION PARAMETERS TEST - Mansyur Efendi; I Made Jiwa Astika; Ayip Rivai Prabowo (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2021)
Several types of zinc anodes have been produced with a variety of different compositions. The variations in the composition of the zinc anode provide different corrosion protection performance. In this study, tested the characteristics of several zinc anode products and their performance in steel corrosion protection. The tests carried out included the composition test using the dry method and the wet method on KRI Zinc, Pure Zinc, and Commercial Zinc. The standard used is the US Military Specification (MIL - A - 18001 - H) standard. In addition to composition testing, the potential difference of each zinc anode is also taken, to determine the potential value of each zinc anode for protection potential, and also for cathodic protection. From the results of the dry composition test, a value that is easy to evaluate is obtained. For testing with the wet method, the value that comes out still needs to be converted to weight percent units. Of the three Zinc, which does not meet the US Mlitary Specification (MIL - A - 18001 - H) standard, namely commercial zinc, because there is an impurity in the form of Fe whose value is greater than the allowable amount of 0.005% according to the US Mlitary Specification (MIL - A - 18001 - H), which can interfere with the performance of the Zinc Anode itself. For the results of the potential difference test, the three Zinc can be used as a sacrificial anode in cathodic protection because there are impurities in the form of Fe whose value is greater than the allowable amount of 0.005% according to the US Military Specification (MIL - A - 18001 - H) standard, which can interfere with the performance of the Zinc Anode itself. For the results of the potential difference test, the three Zinc can be used as a sacrificial anode in cathodic protection because there are impurities in the form of Fe whose value is greater than the allowable amount of 0.005% according to the US Military Specification (MIL - A - 18001 - H) standard, which can interfere with the performance of the Zinc Anode itself. For the results of the potential difference test, the three Zinc can be used as a sacrificial anode in cathodic protection. Keywords: zinc anode, offering anode, protection potential.